The effect of contextual arousal on the integration of emotional words during discourse comprehension. Issue 4 (April 2023) - Zhang, Qian; Mou, Cong; Yang, Xiaohong; Yang, Yufang; Li, Lin
This event-related potential (ERP) study examined the effect of contextual arousal on emotional word integration during discourse comprehension. We used two-sentence discourses as experimental materials. The first sentence served as an emotional context and described a high-arousal positive event, a low-arousal positive event, a high-arousal negative event, or a low-arousal negative event. The second sentence contained one negative word as the critical word, which was identical among different conditions. Thus, four conditions were included in the present study: high-arousal inconsistent, low-arousal inconsistent, high-arousal consistent, and low-arousal consistent. The ERP results showed that inconsistent emotional words elicited larger P200 and LPC than consistent words in the high-arousal context. However, only a P200 effect was observed for inconsistent emotional words in the low-arousal context. Our results indicate that a high-arousal context could lead to more elaborated emotional evaluation in the later stage of emotional word integration and suggest an important role of contextual arousal on the processing of emotional words during discourse processing.